Optimization of photonic crystal waveguide based optical filter - Islam, Pratik Al; Sultan, Nameeza; Nayeem, Seefath; Bhuian, Dr. Md. Belal Hossain (© 2014 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 2014 IEEE Region 10 Symposium, IEEE TENSYMP 2014; Kuala Lumpur; Malaysia; 14 April 2014 through 16 April 2014 [© 2014 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/TENCONSpring.2014.6863017